EFEKTIVITAS MEDIA RELATIONS PT RIAU ANDALAN PULP AND PAPER DALAM MENJALIN HUBUNGAN BAIK DENGAN MEDIA DI PROVINSI RIAU - Sari, Yana; Rasyid, Anuar (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
PT Riau Andalan Pulp and Paper is one of the largest private companies in the worldengaged in pulp and paper so that it is susceptible to getting issues related to environmentaldamage, Media relations is one of the public relations functions that are needed by companiessuch as PT Riau Andalan Pulp and Pulp and Paper . The purpose of this study (1) To determinethe level of effectiveness of media relations PT Riau Andalan Pulp and Paper in establishinggood relations with the media in Riau Province (2) To find out the supporting and inhibitingfactors of PT Riau Andalan Pulp and Paper media relations in establishing good relations withthe media in Riau Province.The method used in this study is mix methods which combines two research methods aswell as quantitative methods supported by qualitative methods, with data collection techniquesnamely through the dissemination of questionnaires to journalists in Riau Province with apopulation of 146 media and a sample of 60 journalists representing 22 media in Riau Province.Data analysis techniques in this study used descriptive statistical techniques and analysistechniques of Miles and Huberman.Based on Jefkins' media relations concept, the indicator of the results of this study showsthe level of effectiveness of PT RAPP's media relations in establishing good relations with highlyeffective media at a scale of 3.28 and supporting and inhibiting factors namely the desire topartner with the media. wherein the company is a dynamic source of news for the media, bothprint and online media, the existence of a business interest in the relationship between thecompany and the media where the limits of fairness and operational limits of work and theinhibiting factors are those which are obstacles to the media the relations officer in carrying outhis strategy in fostering good relations with the media in Riau Province is where there are mediathat have special tendencies and also an element of personal interest by media owners.Keywords: Effectiveness, Media Relations, Mixed Methods